Fabrication and evaluation of hemoglobin-based polydopamine microcapsules as oxygen carriers. Issue 33 (6th April 2018) - Yu, Chunmei; Huang, Xin; Qian, Dongping; Han, Fengfeng; Xu, Linyi; Tang, Yuejing; Bao, Ning; Gu, Haiying
Abstract : Polydopamine-hemoglobin (PDA-Hb) microcapsules possess a high oxygen affinity and could bind and release oxygen reversibly as demonstrated by electrochemical methods. Abstract : Polydopamine-hemoglobin (PDA-Hb) microcapsules as suitable oxygen carriers are fabricated easily by templating decomposable MnCO3 particles in collaboration with self-polymerization of dopamine on pure Hb spheres. The PDA-Hb microcapsules possess a high oxygen affinity and are able to bind and release oxygen reversibly as demonstrated by electrochemical methods.